Analisis Struktur Kinerja dan Kluster Unggulan di Wilayah Kabupaten dan Kota - Tri Eko Darmawan; Arifanny Cindy Saputri; Muhammad Yasin (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
The purpose of this study is to examine the structure of economic performance and identify superior clusters in districts/cities in order to develop a basis for formulating effective regional development strategies. The methodology used is quantitative with a descriptive approach that includes analysis of location quotient (LQ), shift share and class typology. Secondary data comes from official institutions such as the Central Statistics Agency (BPS). The results of the study indicate that Sidoarjo has an advantage in the manufacturing sector (LQ 1.85) and is included in the category of advanced and rapidly developing regions. Lamongan stands out in the agricultural and fisheries sectors with significant growth, although its contribution to GDP is low, it is classified as a rapidly developing region. Gresik has a large and solid commercial sector, but its growth is still lagging behind the national average. Pasuruan is included in the lagging category because its education services sector has not become the mainstay of the economy. The cluster approach has proven successful in identifying regional potential and formulating data-based development policies. Cross-sector collaboration and responsive and supportive government policies are key factors in developing superior clusters that can accelerate regional economic growth in an inclusive and sustainable manner.